1964
DOI: 10.1128/jb.88.4.1071-1077.1964
|View full text |Cite
|
Sign up to set email alerts
|

MORPHOLOGY AND PHYSIOLOGY OF METHANOMONAS METHANOOXIDANS

Abstract: Pure cultures of methane-oxidizing bacteria isolated from soil, from the rumen of a fistulated cow, and from coalmine water were found to be identical in morphological, cultural, and physiological characteristics with Methanoojonas otiethanooxidoans of Brown and Strawinski. Two of the isolates were serologically related to the organism of Brown and Strawinski. All the strains required methane for good growth, but a delayed moderate growth occurred on methanol. No other substanices were utilized as carbon and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1966
1966
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Methane oxidation is observed in some environments such as soil and lakes, and methane-oxidizing bacteria, methanotrophs, have been detected in various environments and characterized (Auman et al 2000;Bull et al 2000). However, little is currently known about methanotrophs in the rumen (Stocks and McCleskey 1964). While approximately 20% of the net global methane flux is oxidized before it can enter the atmosphere (Prather et al 1995), a study using an artificial rumen indicated that only 0AE3% of methane flux is oxidized (Kajikawa and Newbold 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Methane oxidation is observed in some environments such as soil and lakes, and methane-oxidizing bacteria, methanotrophs, have been detected in various environments and characterized (Auman et al 2000;Bull et al 2000). However, little is currently known about methanotrophs in the rumen (Stocks and McCleskey 1964). While approximately 20% of the net global methane flux is oxidized before it can enter the atmosphere (Prather et al 1995), a study using an artificial rumen indicated that only 0AE3% of methane flux is oxidized (Kajikawa and Newbold 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Methane-utilising bacteria have been reported to grow poorly when methanol is the sole source of carbon and energy [1][2][3]. This has been attributed to the accumulation of formaldehyde [4], although the presence of this compound in the culture supernarant of methanol-grown cultures has been observed only when sodium sulphite was used as a trapping agent for formaldehyde [5].…”
Section: Introductionmentioning
confidence: 99%
“…as sole sources of carbon and energy. Facultative methylotrophs can use compounds containing no carbon-carbon bonds as well as complex organic compounds with carbon-carbon bonds as sole sources of carbon and energy (6).Almost all methane-utilizing bacteria isolated in pure culture exhibit obligate growth requirement for methane, methanol, or dimethylether as a source of carbon and energy (5,9,11,19,32,35). Organic compounds were unable to serve as a carbon and energy source.…”
mentioning
confidence: 99%